Monteggia fracture dislocation in adults: study of functional outcome following surgical treatment in patients attending a tertiary care center in North India - Khan, Shameem A. (International Journal of Research in Medical Sciences, 2017)
Background: Monteggia fracture dislocations are rare injuries that comprise less than five percent of all forearm fractures. Good results in monteggia fractures depend on early and accurate diagnosis, rigid fixation of ulna, accurate reduction of radial head and post-operative immobilization to allow ligamentous healing about the dislocated radial head. The objectives of the study were to assess the mean time taken for union of fracture, complication encountered during treatment, to assess the functional outcome and to present conclusions based on the results of plate osteosynthesis of monteggia fracture dislocation in adults. Methods: In a prospective study from September 2013 to August 2016, twenty adult patients of monteggia fracture were admitted and treated by closed reduction/excision of radial head and compression plate fixation of ulna. The results were evaluated by assessing union on serial x-rays at follow-up (6-18 months) and functional outcome using Anderson’s criteria. Results: Most of the cases were type-1 fracture-dislocation according to Bado’s classification. Mean time taken for union was 4.1 months. Using Anderson scoring system, we achieved 65% excellent results, 30% satisfactory result and 5% failure in study case. The complication encountered were superficial infection and non-union. Conclusions: The technique of early closed reduction of radial head and open reduction and internal fixation of ulna using compression plate is a simple and effective means of treating monteggia fracture dislocation in adults with excellent functional outcome. Upper limb should be immobilized in 110-120 degrees of elbow flexion and forearm in supination to prevent radial head redislocation.